ANALISIS YURIDIS RENCANA MERGER PERUSAHAAN JASA TRANSPORTASI ONLINE GRAB DAN GOJEK:(DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA) - Dessy Chindy Narita Sinambela (2021)
Current technological advances affect people's lives in mobilizing from one place, many countries have provided online application-based transportation called ride-hailing, which are useful for meeting drivers with consumers efficiently and practically only through smartphone devices thus encouraging people to make it easier to carry out activities. Due to the Covid-19 pandemic, ride hailing industry have been threatened to terminate their employees, such as Grab has released around 5% of the total number of Grab employees, Gojek has also done the same thing cutting off around 9% of total employees. Various news media have informed that these two companies are alleged to be conducting a merger. The type of ths research is juridical-normative, using secondary data with statutory approach and conceptual approach. The results of this research is confirm that if this horizontal merger occurs, there will be an indication of activities that are prohibited in competition law, namely the dominant firm because the two companies have a high position among competitors in the relevant market, thus the process can be carried out. Therefore, before the merger can conduct these companies should be consultation with the KPPU to prevent cancellations and sanctions resulting from the merger.